TASK APPROACH AND PRINCIPLE PRINCIPLE PERSPECTIVES IN PEDAGOGICAL PROCESSES - THE BASIS OF PROFESSIONAL ACTIVATION STUDENT POSITIONS - Shcherbyna, S.V. (Pedagogy of Higher and Secondary Education, 2022)
This article is devoted to forming of active professional position of future teachers by means of using role perspective principle and problem approach during pedagogical training.